Resurgence of Extra Pulmonary Tuberculosis - Bag, S.; Deep, N; Padhy, S (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: Pulmonary tuberculosis is a public health challenge in the developing Nations. Extra pulmonary tuberculosis (EPTB) is still more challenging. EPTB with co-infection with human deficiencies virus (HIV) and malnutrition further aggravate the problems, the worst human health scenario in 3rd world’s nation. The objective of the study was to explore the magnitude of Extra tuberculosis and to assess the challenge faced in encountering the patient with malnutrition, HIV infection etc. Method: All cases of tuberculosis registered under RNTCP in between 2009 - 2012 in MKCG Medical College, Berhampur, Odisha, India were scrutinized, 2596 case of EPTB were fished out. Details clinical, socio-economic, demographic, HIV status & treatment outcome of these patients were subjected to critical analysis. Results: Even though high prevalence of EPTB is encounter in poor socio-economic, rural back ground and people living with HIV and AIDS, upper and middle classes are not exempted complexities of diagnostic and therapeutic challenges are more often then not observed. Outcome is grim in immune weakened cases. Conclusion: This study emphasized the resurgence of extra pulmonary tuberculosis involving all classes of people in Indian sub-continent. Challenges faced are delineated and determinant of clinical outcome in developing Nations have been highlighted. SAARC J TUBER LUNG DIS HIV/AIDS, 2015; 12(1), Page: 20-24